A DFT study of Co(i) and Ni(ii) pincer complex-catalyzed hydrogenation of ketones: intriguing mechanism dichotomy by ligand field variation. Issue 1 (27th November 2018) - Hou, Cheng; Li, Yinwu; Zhao, Cunyuan; Ke, Zhuofeng
Abstract : Ligand field variation governs the mechanism dichotomy for isoelectronic catalysts. Abstract : The development of earth-abundant transition metal catalysts to replace precious transition metal complexes is highly desired but also challenging. Besides the well-known factors of different metals, different oxidation states, and different electronic configurations, this paper elucidates intriguing mechanistic dichotomy due to another key factor, the ligand field variation. With the Ni(ii ) and Co(i ) pincer complexes as model catalysts (the same d 8 configuration), we systematically studied their differences in coordination geometry, spin state, and mechanistic preference. The mechanisms of ketone hydrogenation mediated by these complexes are systematically investigated. Our results indicate that the Ni(ii ) complex prefers the non-bifunctional inner sphere mechanism via a square planar geometry in singlet state. On the contrary, the Co(i ) pincer complex prefers the bifunctional MLC mechanism via a sawhorse geometry in triplet state. These results are both in good agreement with experimental observations. The interesting mechanism dichotomy can be ascribed to the intrinsic difference in oxidation states and effective nuclear charges between Ni(ii ) and Co(i ), which is reflected in the HOMO–LUMO gaps; this further implies the interplay between the stability and activity of a catalyst. Based on these discoveries, three Ni(ii ) catalyst candidates bearing a functional group at the cis position are proposed and evaluated computationally. The presented study demonstrates the diversity and variability in spin state, coordination geometry, and mechanism for the first-row transition metal catalysts, which is informative for future catalyst design.